A Mixed-Integer Linear Programming for Nodal Clearing Price in Day Ahead Market Considering Security Constraints. Issue 4 (January 2021) - Sun, Guanghui; Wang, Xiaowei; Yang, Libo; Lu, Peng; Ma, Bin; Lv, Hao; Yuan, Long
Abstract: A nodal clearing price model in day ahead market considering security constraints is established. First, the intra-region and inter-region transaction modes are explained, and the order types are shown. The clearing model takes the total social welfare as the goal, considers the security constraints of the network, and specifies the market clearing price expressed by the Lagrangian multiplier. Then the mixed linear programming algorithm is used to solve the model in this paper, and a verification method based on the N-1 criterion is performed. Finally, a numerical case is performed to calculate the clearing price of the network, which illustrates the effectiveness of the proposed method and model.